Do behavior and emotions improve after pediatric epilepsy surgery? A systematic review. (29th April 2019) - Reilly, Colin; Baldeweg, Torsten; Stewart, Neil; Wadhwani, Suresh; Jones, Chloe; Helen Cross, J.; Heyman, Isobel
Abstract: Objective: The objective was to systematically review studies that have focused on behavioral and emotional functioning before (baseline) and after (follow‐up) pediatric epilepsy surgery. Methods: The systematic review was carried out according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) guidelines. PubMed and EMBASE were searched from inception. Findings are described with respect to (1) changes in behavior and emotions between baseline and follow‐up, (2) factors associated with changes in behavior and emotions, and (3) impact of study quality on findings. Results: Fifteen studies met inclusion criteria. The majority of studies employed parent report screening checklists. In these studies, scores were reported to have significantly improved at follow‐up on at least one domain in seven studies and not to have changed significantly in two studies. In no studies was a deterioration in behavior noted. In studies that used Diagnostic and Statistical Manual of Mental Disorders (DSM) clinical diagnoses, no significant change was noted in the numbers of children diagnosed at baseline and at follow‐up. In total, 21 children lost diagnoses, whereas 16 children developed new diagnoses. A better seizure outcome was associated with improvements in behavioral‐emotional functioning at follow‐up in three of the four studies where it was considered. In terms of study quality, none of the studies was rated as strong (ie, had no weak ratings on a quality assessment tool). Significance: There is some evidence of improvement in emotional and behavioral functioning after epilepsy surgery. However, this is confined to scores on parent‐reported screening measures of emotional and behavioral symptoms and not clinical diagnoses. Future research should focus on including responses from multiple respondents (child, parent, teacher) when using screening instruments, but also diagnostic interviews. There is a need for long‐term follow‐up (beyond 2 years) with sufficiently large sample sizes including data from nonsurgery controls to understand factors associated with changes in functioning postsurgery.